Characterization of polyunsaturated fatty acids and antioxidant activity of Vitis vinifera L. (grape) seeds from the Ica Valley, Peru - Felipe Surco-Laos; Jorge A. Garcia; María R. Bendezú; Angel T. Alvarado; Doris Laos-Anchante; Manuel Valle-Campos; Juan F. Panay-Centeno; Juan J. Palomino-Jhong; Paulina Eliades Yarasca-Carlos; Ana María Muñoz; Mario Bolarte-Arteaga; Mario Pineda; et al. (GarVal Editorial Ltda., 2023)
Context: In the Valley of Ica-Peru, the seeds of the fruit of Vitis vinifera L. (grape) are residues from the Pisco Industry, and due to their bioactive compounds, they can represent a new economic and sustainable activity for the population of the mentioned Valley. Aims: To characterize polyunsaturated fatty acids from the seeds of the fruit of Vitis vinifera L. (grape) from the Ica Valley, Peru and determine the antioxidant activity in vitro. Methods: The oil from five grape varieties (Quebranta, Moscatel, Torontel, Mollar, and Italia) was obtained by ethereal extraction with ultrasound. The profile of fatty acids was characterized by gas chromatography with a flame ionization detector (GC-FID). The total polyphenolic content was determined by the Folin-Ciocalteu method and antioxidant activity by two in vitro methods. Results: The values obtained from the 5 grape varieties are presented in a range: total polyphenolic content (TPC: 0.59-154 mg GAE/g); linoleic acid content (69.90-71.87%), oleic acid (18.35-19.90%) and others in a lower percentage (p>0.05). Antioxidant activity: DPPH IC50 38.30-48.43 µL; FRAP 0.49-0.77 μg TEAC/g. TPC/DPPH and TPC/FRAP were significantly different (p<0.05), except for the Mollar TPC/FRAP variety (p>0.05). Conclusions: The oils from the seeds of the Vitis vinifera fruit (grapes) that are residues from the production of Pisco present physicochemical characteristics of oils of high nutritional value with a predominance of polyunsaturated fatty acids and potential antioxidant activity.